Shariah Governance and Maqasid al-Shariah in Islamic Banking: A Systematic Literature Review - Sarah Zettira Agam Darwis; Muh Taufiq; A. Ifayani Haanurat; Ramly Ramly (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Islamic banking is expected not only to comply with formal Shariah requirements but also to realize the higher objectives of Islamic law through accountable, transparent, and socially responsive governance. This study systematically reviews contemporary literature on the relationship between Shariah governance and maqasid al-Shariah in Islamic banking. A structured search and screening process was applied to peer-reviewed studies published between 2020 and 2025. Twenty eligible publications were classified according to research setting, method, governance mechanism, maqasid dimension, and reported outcome. The synthesis identifies five dominant themes: the quality and independence of Shariah supervisory boards, the institutionalization of Shariah review and audit, the operationalization of maqasid-based performance, the linkage between governance and risk management, and the expansion of governance toward sustainability and social value. The findings indicate that strong Shariah governance generally improves compliance quality, stakeholder confidence, financial discipline, and social performance, although evidence remains inconsistent regarding board size, national Shariah boards, environmental outcomes, and standardized measurement. The study proposes an integrated maqasid-oriented governance framework connecting oversight structures, decision processes, disclosure, risk controls, and measurable stakeholder outcomes. The review implies that regulators and Islamic banks should move from procedural compliance toward governance that demonstrates substantive value creation, justice, inclusion, and sustainability.